Diálogos contemporâneos na arquitetura belenense (1979-2007) - Sarquis, Giovanni Blanco (2012)
This research addresses the relationship between modern -understood as revisiting aspects inherent in modern architecture and taken as reference projectual - and regional - adopted as the position of knowledge and interpretation of characteristics of place and external references relevant to the local situation - in architectural production belenense between 1979 and 2007 (considering how to cut the territorial area of Belém, including, besides the metropolitan region of Belém (RMB), the adjacent municipality of Barcarena); investigating how the articulation of these guidelines has contributed to the creation of a segment of contemporary architecture belenense as a result of the review and/or reinterpretation of modern references and regional aspects. Part of the recognition that we can identify as qualitatively different segment of the local architectural production over the period in question, a set of works that, while guided by a pragmatic approach, relies on the support as a modern design (tradition that remains), while establishing constructive dialogues with expressions adapted to the context, to attend in order to adjust the project to the specific environmental of site, especially climate of order. This paper demonstrates that these attitudes, realized in the works - of which twenty were selected for initial analysis, four of which could be subject to further study - are placed as appropriate and linked to the specific circumstances, (re)discussing the modern legacy and updating the discussions on a regional architecture. Thus, the contemporary architecture belenense not be expressed from a comparison between these two issues, but as a dialogue between the regional thematic - not shaped like style, but as staff - and the propositions modern and contemporary architectural designs revealed in architecture projects, in their integration into the site, in the spatial organization of buildings, their structural systems, in their materials and in their environment comfort solutions.